1. Derive “23 + (1 – (7 * 2))” using the following grammar with start symbol < Expression >.You
may apply multiple productions in the same step (in di erent parts of the expression), but you
may not skip steps. Then draw a parse tree.
2. Derive the language of the following grammar with start symbol S. You need to derive
S -> AB
A -> ab | aAb
B -> c | cB
3. Construct a parse table for the following grammar with start symbol A. Using your
parse table, parse the input “abcababc”.
1:A -> BB
2:B -> abC
3:C -> B
4:C -> c
4. Find a grammar describing the following regular expression: (a | b)* |ac